Inulin Improves Insulin Sensitivity, Changes Cecal Bile Acids, but Does Not Mitigate Hepatic Steatosis from an Obesogenic, High Fat Diet. (29th May 2020) - Rust, Bret; Idso, Joseph; Safratowich, Bryan; Bukowski, Michael; Zeng, Huawei; Picklo, Matthew
Abstract: Objectives: Obesogenic, high fat diets (HFD) increase hepatic long chain polyunsaturated fatty acid content (LCPUFA), but also lead to hepatic steatosis and insulin resistance. Fermentable fiber such as inulin (INU) may reduce these negative outcomes via a bile acid (BA)-liver signaling axis. This study tests the hypothesis that INU maintains elevated LCPUFA but reduces HFD-induced insulin resistance and fatty liver and investigates the potential relationship of bile acids. Methods: Male mice (4 wk) were fed a low fat diet (LFD) (16% en fat) or HFD (48% en fat) containing 10% non-fermentable cellulose (CL) or 3% CL and 7% INU for 13 wks in a 2 × 2 factorial design. Tissue, plasma, and cecal contents were collected week 13. Results: Intake of the HFD-CL increased hepatic LCPUFA content and steatosis and reduced insulin sensitivity vs LFD treatments. INU maintained HFD-induced LCPUFA elevation, improved insulin sensitivity, due to reductions in fasting glucose, but did not mitigate HFD-induced hepatic steatosis. When standardized to the hepatic triacylglycerol (TAG) content, LCPUFA (notably 22:6n-3) were increased by INU in the LFD only. The BAs with highest cecal concentrations were deoxycholic (DCA) and beta/omega murine cholic (B/OMCA) acids. INU increased cecal wt and decreased concentrations of DCA and B/OMCA. INU-induced B/OMCA reductions were enhanced by the HFD, but the DCA effects were independent of % en fat. The expression of multiple lipid metabolic genes was assessed. Of these, reductions in Scd1 expression occurred with both HFD and INU treatments compared to LFD-CL. SREBP1c, Fasn, Scd1, Elov5, Fads1, and Fads2 correlated with murine cholic acids and cholic acid in HFD-INU but only weakly in LFD-INU. These relationships were not evident with the CL-based diets. Conclusions: INU in an HFD provided mixed outcomes by maintaining elevated hepatic LCPUFA, reducing fasting plasma glucose concentrations but failing to reduce fasting insulin concentrations and hepatic steatosis. While cecal BAs and hepatic gene expression correlated with the INU treatments, these mechanistic changes did not mitigate HFD-induced hepatic steatosis. Funding Sources: USDA-ARS.